Yield structure, agronomic performance and stability of new potato (Solanum tuberosum) hybrids in western Uttar Pradesh - Pandey, S K; Singh, S V; Manivel, P (The Indian Journal of Agricultural Sciences, 2005)
A study was conducted during 1998-2000 at Modipuram, Uttar Pradesh, with 27 advance generation clones and 8 commercial potato (Solanum tuberosum L .) varieties to evaluate their yield structure, agronomic performance and stability. The total and marketable tuber yield, dry matter and average tuberweight increased with delay in harvesting from 60 to 90 days after planting. Yield increase, however, was faster between 80 and 90 days after planting (130.9 g/plant) than between the other successive days after planting intervals, i e 60 and 70 (87 g/plant) and 70 and 80 (111 g/plant). The increase up to 70 days after planting was owing to increase in number of tubers and average tuber weight, whereas after 70 days after planting it was mainly owing to increase in average tuber weight. Chip colour decreased with maturity. The total tuber yield pooled over 2 seasons and 4 different dates of harvest had significant positive correlation with marketable tuber yield, average tuber weight and tubers/plant and negative with dry matter. Chip colour improved with the increase in tuber dry matter. The ranking of genotypes for total and marketable yield at different dates of lifting varied. Six hybrids, viz 'MS/90- 542', 'MS/89-60', 'MS/91-1326', 'JX 1', 'JX 90' and 'JW 96', and 2 released cultivars 'Kufri Pukhraj' and 'Kufri Sutlej', were identified as suitable genotypes for early crop (60 days). However, for main crop (90 days), the hybrids 'MS/90- 542', 'JX 90' and '85-P-718' and cultivar 'Kufri Pukhraj' were suitable. Two hybrids, 'MS/90-542' and 'JX 90' and 'Kufri Pukhraj' performed well under both early and main harvest. On the basis of stability parameters for all yield and other traits, the advanced hybrids 'MS/89-1095', 'MS/86-89' and 'Kufri Sutlej' for early crop and 'MS/91-1326' and 'Kufri Sutlej' for main crop were ideal genotypes.